Iatrogenic Cushing's syndrome due to nasal betamethasone: a problem not to be sniffed at! - Nutting, CM (1995)
Nasal steroid drops for the treatment of allergic rhinitis can cause iatrogenic Cushing's syndrome and care should be taken with their use in clinical practice.